Femoral hernia in children as a rare pathology: A retrospective case series - Emine Burcu Cigsar Kuzu; Mustafa Onur Oztan; Gokhan Koyluoglu (Wolters Kluwer Medknow Publications, 2023)
Background: Femoral hernias are uncommon groin pathology among children. The rarity of the pathology results in increased complications, delayed diagnosis and inappropriate inguinal exploration. In this study, we review our experience with this surgical entity over a 10-year period. Materials and Methods: The medical records of seven children who underwent femoral hernia repair between January 2010 and January 2021 at a single tertiary centre were retrospectively analysed. Reviewed data included demographics, pre-operative diagnosis, operative technique, complications and follow-up. Results: Seven children (5 females [71%] and 2 males [29%]) were operated due to femoral hernia. Median age was 8 years (range: 3-16 years). Four (57%) patients had right-sided femoral hernia and three (43%) were on the left side. The correct pre-operative diagnosis was obtained in three (42%) cases. The remaining four misdiagnosed cases were diagnosed as femoral hernia at the surgery. In all cases, the initial presentation was swelling; two (28%) had inguinal pain and three patients (42%) required emergency inguinal exploration due to suspected incarceration. All patients had repair of their hernia by open technique; the femoral canal was closed by mesh plug or Vicryl sutures. All patients were discharged without complications. No recurrence was detected and the median post-operative follow-up period was 24 months (range: 8-48 months). Conclusion: Femoral hernia is a challenging pathology and correct diagnosis requires a high index of clinical suspicion. In equivocal cases, ultrasonography and laparoscopy may be useful. Appropriate pre-operative diagnosis evades complications and delays in treatment. Regardless of the surgical approach recurrences and complications are very rare in children.